2023
DOI: 10.3389/fnagi.2023.1131857
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal EEG slowing, synchronization, and ERP peak latency in association with predementia stages of Alzheimer’s disease

Abstract: BackgroundEarly screening of elderly individuals who are at risk of dementia allows timely medical interventions to prevent disease progression. The portable and low-cost electroencephalography (EEG) technique has the potential to serve it.ObjectiveWe examined prefrontal EEG and event-related potential (ERP) variables in association with the predementia stages of Alzheimer’s disease (AD).MethodsOne hundred elderly individuals were recruited from the GARD cohort. The participants were classified into four group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…The outcomes of this study underscore the utilization of machine learning approaches, employing EEG spectral features from task-based data, to distinguish cognitively normal older adults with preclinical AD from cognitively normal controls. While a few studies have noted task-related EEG modifications in older adults with an elevated risk of AD (Arakaki et al, 2019; Choi et al, 2023), these investigations have not incorporated machine learning techniques for group classification. Our study addresses this gap by providing validation that memory-related EEG oscillations can signify neurocognitive changes preceding clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of this study underscore the utilization of machine learning approaches, employing EEG spectral features from task-based data, to distinguish cognitively normal older adults with preclinical AD from cognitively normal controls. While a few studies have noted task-related EEG modifications in older adults with an elevated risk of AD (Arakaki et al, 2019; Choi et al, 2023), these investigations have not incorporated machine learning techniques for group classification. Our study addresses this gap by providing validation that memory-related EEG oscillations can signify neurocognitive changes preceding clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The rhythm of this DMN is intrinsic oscillation, and the functional and anatomical disconnection of DMN could represent a core feature of mild cognitive impairment and postoperative cognitive dysfunction ( Berger et al, 2019 ). Recent study has shown that decreasing of MDF was associated with the pre-dementia stage of Alzheimer’s disease ( Choi et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…For a more explicit prediction of POD, a further study with additional EEG paradigms of event-related potential related to surgery would be useful. Nevertheless, a recent study revealed that eye-closed resting-state EEG features, MDF could be a good indicator of neuro-degeneration and which is advantageous to practicality in real clinical field ( Choi et al, 2023 ). Notwithstanding these limitations, the study suggests that the preoperative MDF is related to POD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These electrodes are positioned according to the 10-20 system map, which includes standard locations such as Fp1 and Fp2 (frontal polar); F3 and F4 (frontal); C3 and C4 (central); P3 and P4 (parietal); O1 and O2 (occipital); F7 and F8 (frontal lateral); T3 and T4 (temporal); T5 and T6 (temporal lateral); and Fz, Cz, and Pz (midline electrodes). To facilitate accurate and efficient electrode placement, an elastic cap embedded with electrodes aligned according to the 10-20 system is often employed [79,80]. This cap ensures consistent positioning and adjusts to different head sizes, significantly enhancing patient comfort during the procedure.…”
Section: Technical Setup and Recording Protocolsmentioning
confidence: 99%